SAT0168 Mri results following discontinuation of methotrexate in patients with rheumatoid arthritis treated with subcutaneous tocilizumab: results from a randomized controlled trial. (12th June 2018) - Peterfy, C.; Kremer, J.; Rigby, W.; Singer, N.; Birchwood, C.; Gill, D.; Reiss, W.; Pei, J.; Michalska, M.
Abstract : Background: Although previous studies have established the efficacy of tocilizumab (TCZ) initiated as monotherapy (MONO) for the treatment of rheumatoid arthritis (RA), 1, 2 changes in active intra-articular inflammation after discontinuation of methotrexate (MTX) in patients achieving good clinical control with TCZ + MTX have not been evaluated. Magnetic resonance imaging (MRI) effectively images synovitis and osteitis and can detect changes in bone erosion with greater sensitivity than radiography. 3 Objectives: This study used MRI to assess differences in joint damage between patients with RA who achieved low disease activity with TCZ + MTX and then continued or discontinued MTX in the COMP-ACT trial (NCT01855789 ). Methods: US patients with RA who were inadequate responders to MTX were enrolled; initial combination therapy included MTX (≥15 mg/week orally) plus TCZ 162 mg subcutaneous (SC) either weekly or every 2 weeks. Patients who achieved DAS28-ESR ≤3.2 at week 24 were randomized 1:1 to receive TCZ-MONO or continue TCZ + MTX until week 52 (double blind). A subset of these patients was included in this MRI substudy; 1.5 Tesla MRI was used to obtain images of bilateral hands and wrists at Weeks 24 and 40. Two independent radiologists evaluated images at a central reading facility using RAMRIS (synovitis, osteitis, erosion) and CARLOS (cartilage loss). Outcomes included changes in MRI scores from Week 24 to 40 and the proportion of patients with progression of each score. Results: Of the 296 patients who achieved DAS28 ≤3.2 at Week 24 and were randomized to TCZ + MTX or TCZ-MONO, 79 were enrolled in the MRI substudy (n = 41 and 38, respectively); 74.7% were women, and the mean (SD) age was 56.3 (12.8) years. Patient demographics in the MRI substudy were similar to overall study demographics. Mean changes from Week 24 to 40 in bone erosion, synovitis, osteitis and cartilage loss scores were not significantly different between the TCZ + MTX and TCZ-MONO groups for both bilateral hands and the dominant hand (table 1 ). There were no significant differences between the groups in the proportion of patients with no progression in each outcome measure (range, 89.7% to 97.4% with TCZ + MTX and 87.9% to 100.0% with TCZ-MONO). Conclusions: In patients who achieved low disease activity with TCZ + MTX, MRI changes were minimal and showed no difference in the response of active intra-articular inflammation in patients who discontinued MTX vs those who continued TCZ + MTX within the period of observation, consistent with the result of similar mean change in DAS28 between the groups in the primary analysis. References: [1]Jones G, et al. J Rheumatol2017;44(2):142–146. [2]Dougados M, et al. Ann Rheum Dis2013;72(1):43–50. [3]Strand V, et al. Arthritis Rheum2013;65(10):2513–2523. Acknowledgements: This study was funded by Genentech, Inc. Disclosure of Interest: C. Peterfy Consultant for: Roche, Employee of: Spire Sciences, Inc., J. Kremer Shareholder of: Corrona, LLC, Consultant for: Abbvie, Amgen, Bristol-Myers Squibb, Eli Lilly and Company, Genentech, GlaxoSmithKline, Pfizer, Regeneron and Sanofi, W. Rigby Consultant for: Roche/Genentech, N. Singer Grant/research support from: Merck/EMD Serono (in kind lab resources) and unrestricted educational grants from several companies to MetroHealth for 2016 Cleveland Society of Rheumatology, C. Birchwood Employee of: Genentech, Inc., D. Gill Employee of: Genentech, Inc., W. Reiss Employee of: Genentech, Inc., J. Pei Employee of: Genentech, Inc., M. Michalska Employee of: Genentech, Inc.